Enhancement of the efficiency of the third harmonic generation process in ZnO:F thin films probed by photoluminescence and Raman spectroscopy. (15th November 2018) - Antony, Albin; Poornesh, P.; Ozga, K.; Jedryka, J.; Rakus, P.; Kityk, I.V.
Abstract: ZnO:F nanostructures at varying fluorine doping concentrations were prepared by spray pyrolysis technique. Effect of fluorine on structure, surface morphology, optical absorption and linear and nonlinear optical properties of the nanostructures were investigated by photoluminescence (PL), raman spectroscopy, THG (third harmonic generation) and Z-Scan analysis. The gaussian fitting on the PL spectra shows different luminescent centers and increase in the intensity. An increase in the PL emission intensity was observed due to the incorporation of fluorine in ZnO lattice which correlates to the formation of various defect states. Prominent emission in the blue, green and violet region along with a weak UV-violet near band edge (NBE) emission was noted in the nanostructures resulted by the Zn and O vacancy defect. ZnO related phonon modes were observed in the raman spectroscopy along with E2 high mode around 439 cm -1 as the signature peak of wurtzite ZnO nanostructures. Z-scan measurements were performed to determine the absorptive and refractive nonlinearity of ZnO:F thin films. The nonlinear optical properties of the ZnO:F thin films found to be enhanced on fluorine incorporation into ZnO lattice. The third order optical susceptibility χ(3) increased from 3.5 × 10 -4 esu to 6.17 × 10 -3 esu due to the enhancement of electronic transition to different defect levels formed in the films. The third harmonic generation studies on ZnO:F thin films were investigated using Nd:YAG laser at a wavelength of 1064 nm and 8 ns pulse width. The THG signal intensity has shown an increment upon fluorine incorporation. The highest value of THG signal was obtained for the 1% ZnO:F thin films. The enhancement of third harmonic response shows that ZnO:F nanostructures finds immense applications in photonic device applications.